2008
DOI: 10.1111/j.1365-2133.2008.08668.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of the novel iron-chelating agent, CP94, to enhance topical photodynamic therapy of nodular basal cell carcinoma

Abstract: Background: Photodynamic therapy (PDT) involves the activation of a photosensitiser by visible light to produce activated oxygen species within target cells, resulting in their destruction. Evidence-based guidelines support the efficacy of PDT using topical 5-aminolaevulinic acid (ALA-PDT) in actinic keratoses, Bowen's disease and basal cell carcinoma (BCC). Efficacy for nodular BCC appears inferior to that for superficial BCC unless prior debulking or repeat treatments are performed.The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…[48,49]. Although these clinical investigations were only designed to assess safety, enhancements in tumour clearance were observed both clinically and histologically when CP94 was included within the photosensitising cream.…”
Section: Introductionmentioning
confidence: 99%
“…[48,49]. Although these clinical investigations were only designed to assess safety, enhancements in tumour clearance were observed both clinically and histologically when CP94 was included within the photosensitising cream.…”
Section: Introductionmentioning
confidence: 99%
“…They also permit insight to the mechanisms that may explain the promising initial clinical results obtained with this enhanced treatment regime in the first clinical safety pilot studies [35][36], as the increased therapeutic effects are most likely being conveyed through the elevated dermal PpIX accumulation observed following effective iron chelation achieved via topical CP94 administration.…”
Section: Discussionmentioning
confidence: 99%
“…This experimentation has been extended here to consider the effect of topical CP94 administration in vivo in a normal rat skin model. In light of our previous findings with CP94 augmentation of PpIX-PDT demonstrated in epidermal squamous carcinoma cells (A431) [30][31], a colonic tumour model [33] and dermatological skin lesions [35][36], it was not deemed necessary to create a neoplastic skin model here when our main focus was to assess PpIX production/excised tissue fluorescence (which we have been unable to do clinically due to ethical constraints).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the iron chelating capacity and toxicity of CP94 have been investigated in a number of iron overloaded and non-overloaded animal models including mice [21,22], rats [23,24], guinea pigs [23], rabbits [25] and Cebus monkeys [24]. Rat studies were found to be predictive of the iron chelating capacity recorded in primates [24] and the metabolism of CP94 in guinea pigs was noted to be more similar to that of humans [23] than studies undertaken in rats as this compound is glucuronidated by the liver and excreted in urine. Topical CP94 administration has been investigated in humans as way of improving PpIX-induced PDT for the treatment of certain non-melanoma skin cancers and precancers.…”
Section: Introductionmentioning
confidence: 99%